Composite engine thrust frame design and manufacturing using fibre steering optimization for launcher structures - Brink, W.M. van den; Maas, R.; Gerrits, W. (Netherlands Aerospace Centre NLR, 2021)
New space launcher systems from ESA will enter a very competitive commercial launcher market. New entrants to this market have reduced the launch price per unit mass payload by half (50%). As a consequence a key requirement for the development of new launchers is reduced recurring production costs and increased performance. A part of the space launcher is the Engine Thrust Frame (ETF), also known as the ViTF (Vinci Thrust Frame). This research was done under lead of Airbus Defense and Space Netherlands and funded by ESA. In line with the launcher’s key requirements the main goal of this research is to save recurring production costs, lower the weight and keep the stiffness requirements of the composite ViTF structure using different innovative design and stiffening techniques, such as fibre steering. The Carbon Fibre Reinforced Plastic (CFRP) full scale reference thrust frame was used as a starting point. Design and optimization of the thrust frame composite layup using the fibre steering method is performed to reduce weight and meet the mechanical requirements. This was followed by detailed analyses and evaluation of the design. For testing purposes the full scale design was scaled down to 1:3 scale. This 1:3 design is manufactured and tested. The optimisation of the full-scale thrust frame design and 1:3 scaled version leads to a significant reduction in weight of 15% compared to the Carbon Fibre Reinforced Plastic (CFRP) reference design. This is achieved by reduction of the amount of blade stiffeners and introduction of the automated fibre steering which results in a more optimal design. The requirements for safety, strength and stiffness are still met with the new design. The optimisation efforts resulted in a design that reached ultimate load without failure and buckling. The tools and methods developed enable next generation composite structures using laminate optimization and fibre steering.